Analyzing and modeling land use/land cover change in Phu Tho Province, Vietnam - Thien, Bui Bao; Phuong, Vu Thi (Journal of Degraded and Mining Lands Management, 2024)
Planning, managing, and developing sustainably all depend on mapping and monitoring changes in land use and land cover (LULC) in Phu Tho Province, Vietnam. In this study, remote sensing and geographic information system (GIS) techniques were employed to track LULC changes in the study area from 1992 to 2022. The supervised classification method in ArcGIS 10.8 software was applied to Landsat satellite data (Landsat 5-TM for 1992 and 2010, and Landsat 9-OLI/TIRS for 2022) to detect and classify five main LULC classes: agricultural land, barren land, vegetation, built-up, and waterbodies. The accuracy of the classification was assessed using kappa coefficients, which were found to be 0.882, 0.891, and 0.915 for the years 1992, 2010, and 2022, respectively. During the period 1992-2022, the areas of agricultural land, built-up, and waterbodies increased by 148.84 km2, 304.15 km2, and 41.04 km2, respectively. However, the areas of barren land and vegetation decreased by 289.39 km2 and 204.64 km2, respectively. Furthermore, the Normalized Difference Vegetation Index (NDVI) and Normalized Difference Built-up Index (NDBI) were utilized to rapidly assess changes in LULC, and their trends were found to be consistent with the supervised classification results. These changes in LULC pose a significant threat to the environment, and the findings of this study can serve as a valuable resource for future land use planning and management in the area.